Improving the Digestibility of Plant Defensins to Meet Regulatory Requirements for Transgene Products in Crop Protection - Parisi, Kathy; Poon, Simon; Renda, Rosemary F.; Sahota, Gurinder; English, James; Yalpani, Nasser; Bleackley, Mark R.; Anderson, Marilyn A.; van der Weerden, Nicole L. (Frontiers in Plant Science, 2020)
Despite the use of chemical fungicides, fungal diseases have a major impact on the yield and quality of plant produce globally and hence there is a need for new approaches for disease control. Several groups have examined the potential use of antifungal plant defensins for plant protection and have produced transgenic plants expressing plant defensins with enhanced resistance to fungal disease. However, before they can be developed commercially, transgenic plants must pass a series of strict regulations to ensure that they are safe for human and animal consumption as well as the environment. One of the requirements is rapid digestion of the transgene protein in the gastrointestinal tract to minimise the risk of any potential allergic response. Here we examine the digestibility of two plant defensins, NaD1 from Nicotiana alata and SBI6 from Soybean, which have potent antifungal activity against major cereal pathogens. The native defensins were not digestible in simulated gastrointestinal fluid assays. Several modifications to the sequences enhanced the digestibility of the two small proteins without severely impacting their antifungal activity. However, these modified proteins did not accumulate as well as the native proteins when transiently expressed in planta, suggesting that the protease-resistant structure of plant defensins facilitates their stability in planta.